Blood pressure measurements, blood pressure variability and endothelial function in renal transplant recipients. (October 2014) - Ozkayar, Nihal; Altun, Bulent; Yildirim, Tolga; Yilmaz, Rahmi; Dede, Fatih; Arik, Gunes; Turkmen, Ercan; Hayran, Mutlu; Aki, Fazil Tuncay; Arici, Mustafa; Erdem, Yunus
Abstract Background/Aims: Hypertension is an important cardiovascular risk factor in renal transplant recipients. Elevated blood pressure variability (BPV) during 24-h ambulatory blood pressure monitoring (ABPM) is associated with increased risk of target organ damage and cardiovascular events, independent of mean blood pressure levels. We aimed to evaluate the relationship between endothelial function, blood pressure levels obtained by various measurement methods, and BPV in renal transplant recipients. Methods: In total, 73 hypertensive renal transplant recipients were included in the study. Office blood pressure measurements, central blood pressure measurements, home blood pressure measurements and 24-h ABPM were obtained from the subjects. BPV was calculated using the average real variability index. All patients underwent brachial flow-mediated vasodilatation tests. Predictive values of blood pressures obtained by different measurement techniques and BPV on endothelial functions were investigated. Results: Endothelial dysfunction was present in 68.5% of the patients. No difference was found between the group with and without endothelial dysfunction with regard to office systolic or diastolic blood pressure, central blood pressure or home systolic blood pressure. In the group with endothelial dysfunction, 24-h ambulatory systolic blood pressure and night-time ambulatory systolic blood pressure were higher. In patients with endothelial dysfunction, the 24-h systolic, diastolic and mean BPV were all higher. There was also a negative correlation between the percentage of flow-mediated vasodilatation with 24-h mean and systolic BPV. Conclusion: Patients with endothelial dysfunction had significantly higher ambulatory blood pressure values and higher BPV. There was a significant negative correlation between endothelial function and BPV.